Lulusan Sekolah Vokasi SMK Negeri 14 Medan dan Kebutuhan Industri Global - Putra, Rismaja (Manajemen dan Bisnis, 2024)
Vocational education is a balanced combination of theory and practice with an orientation towards the work readiness of graduates. Preparing personnel who can establish expertise and skills in their fields, are ready to work and are able to compete globally.training where students will receive hands-on learning to enter their desired field of work. The creation of links and matches between vocational and industrial worlds is the creation of a joint curriculum. Where the curriculum must be synchronized every year with industry.